Intragastric preloads of l-tryptophan reduce ingestive behavior via oxytocinergic neural mechanisms in male mice. (1st June 2018) - Gartner, Sarah N.; Aidney, Fraser; Klockars, Anica; Prosser, Colin; Carpenter, Elizabeth A.; Isgrove, Kiriana; Levine, Allen S.; Olszewski, Pawel K.
Abstract: Human and laboratory animal studies suggest that dietary supplementation of a free essential amino acid, l -tryptophan (TRP), reduces food intake. It is unclear whether an acute gastric preload of TRP decreases consumption and whether central mechanisms underlie TRP-driven hypophagia. We examined the effect of TRP administered via intragastric gavage on energy- and palatability-induced feeding in mice. We sought to identify central mechanisms through which TRP suppresses appetite. Effects of TRP on consumption of energy-dense and energy-dilute tastants were established in mice stimulated to eat by energy deprivation or palatability. A conditioned taste aversion (CTA) paradigm was used to assess whether hypophagia is unrelated to sickness. c-Fos immunohistochemistry was employed to detect TRP-induced activation of feeding-related brain sites and of oxytocin (OT) neurons, a crucial component of satiety circuits. Also, expression of OT mRNA was assessed with real-time PCR. The functional importance of OT in mediating TRP-driven hypophagia was substantiated by showing the ability of OT receptor blockade to abolish TRP-induced decrease in feeding. TRP reduced intake of energy-dense standard chow in deprived animals and energy-dense palatable chow in sated mice. Anorexigenic doses of TRP did not cause a CTA. TRP failed to affect intake of palatable yet calorie-dilute or noncaloric solutions (10% sucrose, 4.1% Intralipid or 0.1% saccharin) even for TRP doses that decreased water intake in thirsty mice. Fos analysis revealed that TRP increases activation of several key feeding-related brain areas, especially in the brain stem and hypothalamus. TRP activated hypothalamic OT neurons and increased OT mRNA levels, whereas pretreatment with an OT antagonist abolished TRP-driven hypophagia. We conclude that intragastric TRP decreases food and water intake, and TRP-induced hypophagia is partially mediated via central circuits that encompass OT.